Assessing modern river sediment discharge to the ocean using satellite gravimetry - Maxime Mouyen (Nature Portfolio, 2018)
Measuring rivers’ sediment discharge is critical to assess continental erosion and landscape dynamics, yet it remains a challenging task. Here the authors show that GRACE satellite helps quantifying river sediment discharge by measuring the increment in gravitational attraction due to sediment accumulation.